Scientific production of the "Revista Cubana de Estomatología" in 2018 - Alain Manuel Chaple Gil; Josefa Dolores Miranda-Tarragó (Editorial Ciencias Médicas, 2019)
The Cuban Journal of Stomatology, official organ of the Cuban Society of Stomatology; It has the mission of publishing scientific articles that report on the development of dental sciences for the benefit of the health of the population. We take the opportunity to share with our readers the results of the previous year.